2020
DOI: 10.1109/access.2020.2996687
|View full text |Cite
|
Sign up to set email alerts
|

On Stabilization of Linear Switched Singular Systems via P-D State Feedback

Abstract: Impulsive phenomenon and state jumps at switching instants are inevitable control difficulties in the study of stability for switched singular systems. Proportional-derivative (P-D) state feedback may be an effective way to eliminate impulsive behaviors and state jumps. In this work, the problem of stabilization is studied for switched singular systems in the continuous-time case and discrete-time case. A synchronous design method of P-D state feedback controllers is proposed by introducing some free-weighting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Many real-world systems can be modelled as switched singular systems [3], such as switching power converters, networked control systems, traffic systems. In recent years, switched singular systems have attracted considerable attention of many scholars, and plenty of research results have been reported [1]- [6].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many real-world systems can be modelled as switched singular systems [3], such as switching power converters, networked control systems, traffic systems. In recent years, switched singular systems have attracted considerable attention of many scholars, and plenty of research results have been reported [1]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…For any two singular subsystems, due to the existence of algebraic equations, the state variables at switching points may be not the consistent initial condition of the next activated subsystem, which will inevitably lead to state jump at the switching instant [9]. Simple state feedback or output feedback can hardly eliminate the impulsive behaviors and state jumps at switching instants [6]. Therefore, many research results on switched singular systems were obtained under assumptions that the states do not jump at switching instants [14], [20], [21] and all singular subsystems are impulse-free [22], [23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations